2013
DOI: 10.1177/0731684413483886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different acid solutions on glass/epoxy composites

Abstract: Composite materials are exposed to a range of hostile environments with consequent degradation in terms of mechanical properties. However, the bibliography is not sufficient to establish a full knowledge about the effect of hostile environments on mechanical properties. This work intends to study the response to flexural and to low velocity impact of a glass fibre/epoxy composite after immersion in two different acid solutions, hydrochloric acid and sulphuric acid. These solutions affect significantly the flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 30 publications
9
27
0
1
Order By: Relevance
“…Moreover, Amaro et al [13] analysed the effect of alkaline (NaOH) and acid (HCl) solutions on the flexural properties of these composites, and the worst bending properties were obtained when the glass/epoxy composites were exposed to NaOH solutions. The effect of hydrochloric acid (HCl) and sulphuric acid (H 2 SO 4 ) was also compared by these authors, and the HCl solution was responsible for the poorest results [14]. Similar conclusions were also obtained by Kamal and Kadhim [15] on nano-silica-reinforced (glass/Kevlar) fabric polyester hybrid composites, due to the higher corrosive effect of alkaline solutions.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, Amaro et al [13] analysed the effect of alkaline (NaOH) and acid (HCl) solutions on the flexural properties of these composites, and the worst bending properties were obtained when the glass/epoxy composites were exposed to NaOH solutions. The effect of hydrochloric acid (HCl) and sulphuric acid (H 2 SO 4 ) was also compared by these authors, and the HCl solution was responsible for the poorest results [14]. Similar conclusions were also obtained by Kamal and Kadhim [15] on nano-silica-reinforced (glass/Kevlar) fabric polyester hybrid composites, due to the higher corrosive effect of alkaline solutions.…”
supporting
confidence: 61%
“…Moreover, they also reported that this behaviour is strongly affected by the fibre orientation [37,[41][42][43][44], temperature [37,41,42,44] and environment [45]. In fact, Amaro et al [13,14] and Reis et al [45] observed a significant decrease on the flexural strength and higher stress relaxation due to fibre/matrix interface degradation that was promoted by the immersion of the composite into acid and alkaline solutions. Hence, it is clear that the Polymers 2020, 12, 20 3 of 12 interface properties play a relevant role on stresses, because relaxation occurs due to the breaking of bonds and their propagation [46].…”
mentioning
confidence: 98%
“…The roughness increased with the exposure time and was higher for the samples immersed in alkaline solutions. The effect of different acid solutions was studied, in a similar work, by the same authors [5]. In this case, a hydrochloric acid (HCl) and a sulphuric acid (H 2 SO 4 ) were used and the flexural properties were affected significantly by these solutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, low velocity impact associated with highly corrosive environments, is reported in bibliography only by Amaro et al [4,5] on glass/epoxy composites. According with these authors, the resistance of the glass/epoxy laminates to repeated low velocity impacts is very dependent of the corrosive environment and the exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the amine-cured epoxies can cure at ambient conditions and are known as the most common coatings for metal equipment and concrete constructions under corrosive environments [1]. When these coatings are used in chemical solutions such as process fluids in chemical plants and sewage water in communities, the water and solute molecules gradually penetrate into the epoxy resins, especially under low pH acid conditions [2][3][4][5][6][7]. After the penetrants reach the interface between the resin coating and the substrate, the substrate can be corroded by the penetrants.…”
Section: Introductionmentioning
confidence: 99%